Effects of Seasonal Upwelling on Inorganic and Organic Matter Dynamics in the Water Column of Eastern Pacific Coral Reefs - Stuhldreier, Ines (2015)
The Gulf of Papagayo at the northern Pacific coast of Costa Rica experiences pronounced seasonal changes in water parameters caused by wind-driven coastal upwelling. While remote sensing and open water sampling already described the physical nature of this upwelling, the spatial and temporal effects on key parameters and processes in the water column have not been investigated yet, although being highly relevant for coral reef functioning. The present study investigated a range of water parameters on two coral reefs with different exposure to upwelling (Matapalo and Bajo Rojo) in a weekly to monthly resolution over one year (May 2013 to April 2014). Based on air temperature, wind speed and water temperature, three time clusters were defined: a) May to November 2013 without upwelling, b) December 2013 to April 2014 with moderate upwelling, punctuated by c) extreme upwelling events in February, March and April 2014. During upwelling peaks, water temperatures decreased by 7°C (Matapalo) and 9°C (Bajo Rojo) to minima of 20.1 and 15.3°C respectively, while phosphate, ammonia and nitrate concentrations increased 3 to 15-fold to maxima of 1.3 μmol PO4 3- L-1, 3.0 μmol NH4 + L-1 and 9.7 μmol NO3 - L-1. This increased availability of nutrients triggered several successive phytoplankton blooms as indicated by 3- (Matapalo) and 6-fold (Bajo Rojo) increases in chlorophyll a concentrations. Particulate organic carbon and nitrogen (POC and PON) increased by 40 and 70% respectively from February to April 2014. Dissolved organic carbon (DOC) increased by 70% in December and stayed elevated for at least 4 months, indicating high organic matter release by primary producers. Such strong cascading effects of upwelling on organic matter dynamics on coral reefs have not been reported previously, although likely impacting many reefs in comparable upwelling systems.